KONTRUKSI PT-Symmetry MULTI DIMER PADA DOMAIN TAK HINGGA - Maya Sari Syahrul; Iswan Rina; Nurweni Putri (LPPM Universitas Bina Bangsa, 2023)
Parity-Time Symmetry, or abbreviated as -Symmetry, can be explained as the propagation of an optical beam in two bound waveguides, where one waveguide experiences strengthening and the other waveguide experiences weakening, with each intensity having the same value. Then, the two waveguides are known as dimers, so the phenomenon is called dimer -Symmetry. Furthermore, the -Symmetry dimer is expanded into a system consisting of a collection of -Symmetry Dimers, where each dimer is bound by a binding constant. The result of this expansion is called the multi dimer -Symmetry system. Research on the propagation of optical rays in waveguides plays an important role in the development of optical-based communication technology in the future